Being seduced:: Trainee therapists’ reactions to and handling of client sexual attraction in therapy - Luca, Maria (European Journal for Qualitative Research in Psychotherapy, 2018)
This study explored how trainee therapists react to and handle client sexual attraction (SA) in their work. Qualitative interviews were conducted with 12 volunteer trainees of counselling psychology and psychotherapy who responded to an advert. Transcripts were analysed using constructivist grounded theory (GT). The conceptual stages developed highlight the difficulties trainees experience in relation to client sexual attraction: conflicting feelings and anxious professional beliefs encapsulated in moralistic reactions, culminating in defensive handling of sexual attraction. These psychological conditions seem to be a strategy for professional survival. The trainee experience is captured in the core category: Moralistic Responses to Sexual Attraction and Defensive Handling, associated with a climate of fear that client sexual attraction could potentially influence the therapist into behaving unethically. The study found that trainees believe that professionalism is free of sexual feelings whether these are client, therapist or mutual.